How to turn a state into the tool of revolution: the creation of the Soviet Socialist Republic of Lithuania and Belarus in 1919 - Mickys, Paulius Julius (Vilnius University Open Series, 2024)
Soviet Socialist Republic of Lithuania and Belarus (SSR LiB) is one of the strangest and least understood periods in a turbulent history of Lithuania of the beginning of the 20th century. This paper aims to tackle stereotypes surrounding the Litbel, which are not always able to explain some of the more puzzling elements of the life of the puppet republic. The soviet quasi–state is examined primarily through the lens of the role of instrument of revolution assigned to it. One can distinguish several different ways in which the Bolsheviks hoped to use the territory of Lithuania and Belarus, to which a state–like organizational form was given. Although the Bolsheviks originally brought the SSR LiB to life as a diplomatic weapon for the protection of Soviet Russia, communist leaders were quick to exploit the territory of the new soviet republic for their strategic, military, as well as economic gains. The pursuit of the aforementioned gains was not in the least compatible with the interests and needs of the local population. However, the specific communist thinking, which viewed all political units almost solely as instruments of revolution, did not allow for even a slightest comparison between local problems and the ultimate goal of victory for the socialist revolution, which was viewed as infinitely more valuable.